2017
DOI: 10.22161/ijeab/2.5.60
|View full text |Cite
|
Sign up to set email alerts
|

Potential of silicon fertilization in the resistance of chestnut plants toink disease(Phytophthora cinnamomi)

Abstract: The European chestnut (Castanea sativa Mill.) is a specie with great economic importance in Europe that have been present for thousands of years. In Portugal, the chestnut helps to maintain a positive trade balance, by contributing to the gross national product (GDP). One of the biggest threats for the chestnut is the ink disease caused by Phytophthora cinnamomi, this disease is problematic to chestnut crop with a damaging impact. Silicon (Si) is classified as a beneficial nutrient, having the ability to make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The accumulation of leaf Si still was improved on the B-32°C phase, with an increase of 314%, 439%, and 568% on 5 mM, 7.5 mM, and 10 mM SiK®, relatively to control. The present findings show that there was a positive relationship between SiK® content in fertilization and the leaf content of Si, indicating that the chestnut species is a siliceous species, as was also suggested by Carneiro- Carvalho et al (2017).…”
Section: Silicon In Leavessupporting
confidence: 87%
“…The accumulation of leaf Si still was improved on the B-32°C phase, with an increase of 314%, 439%, and 568% on 5 mM, 7.5 mM, and 10 mM SiK®, relatively to control. The present findings show that there was a positive relationship between SiK® content in fertilization and the leaf content of Si, indicating that the chestnut species is a siliceous species, as was also suggested by Carneiro- Carvalho et al (2017).…”
Section: Silicon In Leavessupporting
confidence: 87%
“…Three treatments were carried out: Ctrees didn't receive any potassium silicate (SiK®); SS and SL -15 L of SiK® at 10 mM SiK® concentration was respectively applied: to the soil or sprayed directly to the leaves. The SiK® solution was prepared in the laboratory according to Carneiro-Carvalho et al (2017) and after was adjusted the solution to pH 6.9 using 30 M hydrochloric acid (HCl). The SiK® concentration used was the one that presented the best results in previous studies (Carneiro -Carvalho et al, 2017).…”
Section: Silicon Treatmentsmentioning
confidence: 99%
“…The SiK® solution was prepared in the laboratory according to Carneiro-Carvalho et al (2017) and after was adjusted the solution to pH 6.9 using 30 M hydrochloric acid (HCl). The SiK® concentration used was the one that presented the best results in previous studies (Carneiro -Carvalho et al, 2017).…”
Section: Silicon Treatmentsmentioning
confidence: 99%
“…Although the effectiveness of silicon (Si) in the control of plant diseases, as well as its mode of action, are not very well understood. Carneiro-Carvalho et al (2017) reported that Si appears to be a possible inducer of resistance to P. cinnamomi in chestnut trees. Previous in vitro studies, performed by Kaiser et al (2005), also found that 5 ml soluble Si per litre of agar inhibited the growth of P. cinnamomi by 100%.…”
Section: Introductionmentioning
confidence: 99%